Research on the Integration of Physical Education Teaching and Health Education in Practice - Hu, Wentao (Journal of Theory and Practice of Social Science, 2023)
In the process of modernization in the 21st century, the importance of health is self-evident, and the development of health education in China's education system has also become a focus of attention from all sectors of society. Primary and secondary education has gradually shifted from focusing solely on students' academic performance to focusing on their physical health, which is of great practical significance for promoting students' comprehensive development. In this regard, primary and secondary education needs to fully leverage the advantages of physical education, deepen the integration mechanism of health education and physical education teaching, and systematically integrate health education into physical education teaching, allowing students to fully understand the lifestyle of health education, in order to strengthen students' health awareness and improve their learning quality. The article conducts practical research on the integration of physical education teaching and health education, aiming to provide reference suggestions for the organic integration of the two.